Extraction Mudarabah from IFI: Reposition of Mudarabah as a Cooperation System of Islamic Socio-Economics - Nurohman, Dede (EQUILIBRIUM, 2022)
Mudarabah is the core of the Islamic cooperation system, which is expected to improve people's welfare. Its practice in Islamic Financial Institutions (IFI) has not realized that goal. One reason is forcing this system to become a profit-oriented formal financial institution. This paper aims to reveal the problems of the institutionalization of mudarabah and attempt to reposition it from IFI to a cooperation system of Islamic socio-economic so that the lofty goals of this system can be realized. This research uses literature and field studies. Data mining techniques use documentation, interviews, and participant observation. The research findings show that four aspects are applied in worksheets that conflict with the essential characteristics of mudarabah, namely, capital and determination of profit sharing, business management, determination of business period, and guarantees. Efforts to reposition mudarabah into the cooperation system of Islamic socio-economic are carried out by removing mudarabah from the IFI and allowing it to become a cultural system that facilitates community needs in economic interaction or to become a cooperation system within the Baitul Mal which positions the Baitul Mal as nothing more than a facilitator that brings together sahibul mal and mudarib.